EXAMINATION IN AUDITING. - Meigs, Walter B. (The Accounting Review, 1963)
Abstract The auditing section of the May,1964 Uniform Certified Public Accountants (CPA) examination was given May 14, 1964 and included seven questions. Answers which follow are intended to typify those submitted by well-prepared candidates writing within approximately the time limits prescribed. They do not necessarily include all elements for which credit might be given by the Advisory Grading Service of the American Institute of CPA's or by the various state accountancy boards charged with responsibility of issuing CPA certificates. Some of the questions were, When no audit has been performed, any financial statements with which a CPA's name is associated should be conspicuously marked on each page as audited. When such statements are accompanied by his explanatory comments, the CPA must, five options were been provided. Another question was, when a CPA is examining the consolidated financial statements of a parent company and is utilizing the unqualified report of another CPA for a domestic subsidiary of material importance, the principal CPA, again five options were provided for correct answer.